PSI-23 In vitro fermentation characteristics for Cheatgrass (Bromus tectorum L.) and Medusahead (Taeniatherum caputmedusae L.) harvested on Idaho rangeland in different seasons. (5th December 2019) - Jensen, Scott; Myers, Cheyanne A; Chibisa, Gwinyai
Abstract: Grazing could be used to control invasive grass species on rangeland. However, the characterization of the seasonal changes in the nutritive value of the invasive grass species will enable the development of targeted grazing strategies. Therefore, the objective of this study was to determine the in vitro fermentation characteristics of Cheatgrass (Bromus tectorum L.) and Medusahead (Taeniatherum caputmedusae L.) harvested on Idaho rangeland. Forage samples were collected from the Reynold Creek watershed (Owyhee county, ID) in summer (June 2018), fall (September 2018) and winter (January 2019). A batch culture system was then used to evaluate volatile fatty acid (VFA) production (6 h), and in vitro dry matter (IVDMD) and NDF digestibility (IVNDFD; 24 h and 48 h). All data was analyzed using the MIXED procedure of SAS. There was no season or grass species effect (P ≥ 0.24) on total VFA concentration and the molar proportion of acetate. However, there was a season × grass species interaction (P = 0.04) for the molar proportion of propionate; it was higher for cheatgrass than medusahead in summer, but not in winter and fall. Both season and grass species had no effect (P ≥ 0.11) on the molar proportions of butyrate, valerate, and total branch chain VFA. There was a season × grass species interaction for 24 and 48 h IVDMD and 24 h IVNDFD (Table 1). In addition, 48 h IVNDFD was greater (P < 0.01) when grasses were harvested during the summer compared to the fall and winter seasons. In summary, although there were no differences across invasive grass species when harvested during the fall and winter seasons, the molar proportion of propionate, 24 and 48 h IVDMD and 24 h IVNDFD were greater for cheatgrass compared to medusahead when harvested in summer.